SNPs of dammarenediol synthase gene were associated with the accumulation of ginsenosides in DAMAYA ginseng, a cultivar of Panax ginseng C. A. Mey. (September 2016) - Cheng, Chunsong; Wu, Wenru; Huang, Baoming; Liu, Liang; Luo, Pei; Zhou, Hua
Graphical abstract: Highlights: 18 ginsenosides were detected simultaneously by UHPLC coupled with TOF/MS. SNPs on DS gene are associated with the accumulation of ginsenosides. SNP loci of 279 play a major role in ginsenosides regulating. Leu83aa mutant (target mutation) could cause functional change of DS gene. Abstract: Context: Ginsenosides are regarded as the major active ingredients of ginseng, the dried taproot of Panax ginseng C. A. Mey. Our previous study has shown that several single nucleotide polymorphisms (SNPs) loci were identified in dammarenediol synthase (DS) gene, a key enzyme in the biosynthetic process of ginsenoside. Objective: The current study aims to investigate the possible influence of SNPs on the content of ginsenosides in DAMAYA ginseng, a cultivar of P. ginseng . Materials and methods: We selected a particular group of DAMAYA ginseng samples that were harvested in the same place of origin for SNP analysis, and then analyzed 18 ginsenosides in these samples with ultrahigh pressure liquid chromatography (UHPLC) coupled with time-of-flight mass spectrometer system (TOF/MS). Results: We found that these SNPs are associated with the accumulation of active ingredients ginsenosides Rf, Rg1 and F1. Moreover, OPLS-DA analysis implied that SNP loci of 279 might play a role in influencing the content level of ginsenosides. Further bioinformatics analysis showed that Leu83aa mutant might cause structural and functional changes of DS gene, which could in turn result in the content change of dammarane ginsenosides. Discussion and conclusion: Our findings suggest that specific SNPs of DS gene might be associated with the accumulation of some ginsenosides in DAMAYA ginseng and thus can be used for varietal characterization, molecular identification, qualitative evaluation of ginseng-type medicinal materials, or gene engineering and ginseng breeding.